Infections of the Spine and Spinal Cord in Children - Kara, Simay A.; Choudhary, Gagandeep; Udayasankar, Unni K. (Journal of Pediatric Neurology, 2017)
Infection of the spine and spinal cord are uncommon in children which if not diagnosed and treated early in the course of disease can lead to spinal instability and devastating neurological outcome. The spectrum of spinal infection ranges from discitis/osteomyelitis, spinal epidural abscess, subdural abscess, spinal meningitis, arachnoiditis, neuritis, myelitis, and intramedullary abscess. Inability of the children to express themselves and nonspecific clinical features like abdominal pain, walking/crawling difficulty, and fever can result in difficult and delayed diagnosis. Imaging plays a critical role in diagnosis of spinal infection; its complication and treatment follow-up. Magnetic resonance imaging with gadolinium contrast is considered as the imaging modality of choice for evaluation of spinal and cord infections. Infectious mimics like chronic recurrent multifocal osteomyelitis, pars articular defect with active inflammatory changes, spondyloarthritis, Guillain-Barre syndrome, transverse myelitis, acute disseminated encephalomyelitis, and multiple sclerosis can pose diagnostic challenge on imaging. The aim of this article is to briefly review the imaging appearances of infection involving various spinal compartments, pattern of infection spread, its complications and various mimics.
Keywords: spine; spinal cord; infectious; meningitis; osteomyelitis